Receptor for Advanced Glycation End Products (RAGE): A Pivotal Hub in Immune Diseases - Qing Yue; Yu Song; Zi Liu; Lin Zhang; Ling Yang; Jinlong Li (Molecules, 2022)
As a critical molecule in the onset and sustainment of inflammatory response, the receptor for advanced glycation end products (RAGE) has a variety of ligands, such as advanced glycation end products (AGEs), S100/calcium granule protein, and high-mobility group protein 1 (HMGB1). Recently, an increasing number studies have shown that RAGE ligand binding can initiate the intracellular signal cascade, affect intracellular signal transduction, stimulate the release of cytokines, and play a vital role in the occurrence and development of immune-related diseases, such as systemic lupus erythematosus, rheumatoid arthritis, and Alzheimer’s disease. In addition, other RAGE signaling pathways can play crucial roles in life activities, such as inflammation, apoptosis, autophagy, and endoplasmic reticulum stress. Therefore, the strategy of targeted intervention in the RAGE signaling pathway may have significant therapeutic potential, attracting increasing attention. In this paper, through the systematic induction and analysis of RAGE-related signaling pathways and their regulatory mechanisms in immune-related diseases, we provide theoretical clues for the follow-up targeted intervention of RAGE-mediated diseases.